Visualizing syntenic relationships among the hemiascomycetes with the Yeast Gene Order Browser - WOLFE, KENNETH (Oxford University Press, 2006)
The Yeast Gene Order Browser (YGOB) is an online tool designed to facilitate the comparative genomic visualization and appraisal of synteny within and between the genomes of seven hemiascomycete yeast species. Three of these genomes are polyploid, and hence contain intra-genomic syntenic regions, the correct assembly of which is a particular success of YGOB. Designed to accurately assemble, display and score gene order relationships, YGOB is both an interactive tool for browsing genomic data, and a software engine now being used for evolutionary analyses on a whole-genome scale. Underlying the online interface is the YGOB database, which consists of homology assignments across the species, extensively curated based on sequence similarity and novelly, an appraisal of genomic context (synteny) in multiple genomes. Currently the YGOB database incorporates genome data from Saccharomyces cerevisiae, Candida glabrata, Saccharomyces castellii, Ashbya gossypii, Kluyveromyces lactis, Kluyveromyces waltii and Saccharomyces kluyveri, but the system is scaleable to accommodate additional genomes. This paper discusses the usage and utility of version 1.0 of YGOB, which is publicly available at http://wolfe.gen.tcd.ie/ygob.
PUBLISHED
Keywords: Human genetics